Chronic subdural hematomas: challenges and solutions. Part I. Clinical variants and diagnosis - Leonid B. Likhterman; Aleksandr D. Kravchuk; Vladimir A. Okhlopkov (LLC "MEDIAFORMAT", 2021)
Chronic subdural hematoma (cSDH) is a multifactorial extensive intracranial hemorrhage, causing the local and/or general brain compression. Hematoma has a delimiting capsule, which defines all pathophysiological features, clinical course and treatment tactics. The paper reports contemporary views on ethiology and clinical course of cSDH. Emphasis is placed on the diagnosis. Based on the analysis of 558 verified cSDH observations, the phasal course and brain imaging data are reported. CT and MRI signs of cSDH are defined.